Penguatan Karakter Bangsa Melalui Program Projek Penguatan Profil Pelajar Pancasila dalam Mewujudkan Pelajar Berkarakter Pancasila - Kartika Dwi, Rianingsih; Rizki Laily Alifiyah; Zahrah Qonitah Kusnadi; Devi Irnafa Zuhro; Fannia Fatma Cahyani; Muhammad Turhan Yani (Lembaga Einstein College (LEC), 2025)
The progress of a nation is not only determined by economic and military strength, but also supported by the character of its citizens. In the context of Indonesia, strengthening character based on Pancasila values is the main foundation for building a strong and sustainable national resilience. This study aims to examine in depth the strategic contribution of the Pancasila Student Profile Strengthening Project Strengthening the Profile of Pancasila Students (P5) Project as an instrument for transforming the character of young people in responding to the challenges of moral degradation and globalization of values. Using a descriptive qualitative approach based on literature review, this study examines the relationship between the dimensions of P5 character and the development of high-quality human resources with a Pancasila ideology. The results The study shows that P5 substantively forms six main character dimensions: faith and piety to God Almighty, independence, cooperation, global diversity, critical thinking, and creativity. Each dimension is not only instilled through cognitive learning, but also developed through a collaborative and reflective approach that position students as active subjects in education. The implementation of P5 has proven effective in reviving the values of cooperation, fostering tolerance, and enhancing critical thinking and creative thinking skills among students. Beyond the curricular program, P5 is a strategic national design to prepare the golden generation of who are adaptive, have integrity, and actively contribute to the life of the nation and state. Thus, character building through P5 is a long-term ideological and cultural investment in order to realize a strong, independent, and dignified Indonesia at the global level